Port site recurrence after laparoscopic adrenalectomy for metastatic melanoma - Saraiva,Pedro (2003)
Port site metastasis after adrenal surgery is a rare entity. We describe the case of a 70-year-old man with a solitary adrenal metastasis from malignant melanoma, which was laparoscopically removed. Twelve months later, he presented a recurrence near one of the laparoscopic port sites. This lesion was surgically removed and after a 18-month follow-up, the patient presents no evidence of disease.